Diameter dependence of the optoelectronic properties of single walled carbon nanotubes determined by ellipsometry. (March 2015) - Battie, Y.; Broch, L.; En Naciri, A.; Lauret, J.-S.; Guézo, M.; Loiseau, A.
Abstract: We report ellipsometric measurement on single walled carbon nanotube (SWCNT) films performed in a large spectral range from 0.07 to 4.97 eV. The complex dielectric functions of SWCNTs are correlated to their diameter distribution extracted from transmission electron microscopy. Here we show that the transition energies between Van Hove singularities are directly related to the strong one dimensional confinement. In the infrared spectral range, the real part of the dielectric function becomes negative. The electronic properties of SWCNTs are extracted from ellipsometry by using a Drude model. The mobility and the mean free path of charge carriers are limited by the high number of SWCNT contacts. In accordance with tight binding simulation, the conductivity and the charge carrier concentration increase with the SWCNT diameter. Finally, we demonstrate that the π-plasmon energy depends on the charge carrier concentration.